Transitioning to a communication-oriented pedagogy: Taiwanese university freshmen's views on class participation. (April 2015) - Hsu, Wen-Hsien
Abstract: This study investigated 354 Taiwanese university freshmen's attitudes toward oral participation in the English as a foreign language (EFL) classroom as they transitioned to an English-medium, communication-oriented pedagogy. It aimed to elucidate the causes of students' participation and non-participation in class discussions and the relationship between participation and English language performance. Data were gathered from two questionnaires and two English performance measures. Results showed that students' class participation significantly correlated with their course achievement and English listening proficiency. In addition, they revealed an apparent contradiction between students' views and their reported behaviors. Though students valued class participation and were reluctant to be passive learners, they demonstrated low overall involvement. Analysis further suggested that limited verbal contributions to class discussion among EFL students may signal an evolving desire for learner autonomy and active participation deterred by a complex mix of linguistic and non-linguistic variables. On the other hand, students indicated that being prepared for class, feeling assured of their answers before speaking, and engaging in small group activities were conducive to participation. This study proposes several pedagogical implications to aid instructors in promoting second and foreign language students' engagement and learning outcomes in a communication-oriented pedagogy.